Mineral fertilizer use in land-scarce conditions: case of Rwanda - Mugabo, J.R.; Tollens, E.; Chianu, Jonas N.; Vanlauwe, Bernard (Walter de Gruyter GmbH, 2020)
This study was undertaken to investigate the use of mineral fertilizer by smallholder farmers in order to understand the set of factors influencing the decisions of smallholder farmers to use fertilizers in land-scarce conditions. Using descriptive analysis and the Cragg’s double-hurdle model, the study identified and analyzed factors that determine smallholder farmer adoption of mineral fertilizers and those that affect the intensity of household mineral fertilizer use. From factors that only influence the decision of smallholder farmers to use mineral fertilizers, distance to fertilizer market and livestock affects it negatively; while farmer association membership, landholding per capita, access to extension services and the size of household affect it positively. The variable “domestic assets” which is a proxy variable for smallholder farmers’ wealth affects only the intensity of use of mineral fertilizers. Literacy of head of household, share of potatoes sold and extension services have an effect on the probability of adoption and intensity of mineral fertilizer use. Improving smallholder farmers’ access to information (extension services and education) and increasing mineral fertilizer profitability through improving agricultural commodity markets are essential for raising both the adoption of mineral fertilizers and the extent of mineral fertilizer use among smallholder farmers in Rwanda.